Conflicts between humans and crocodilians in urban areas across Brazil: a new approach to support management and conservation - Mascarenhas-Junior, Paulo; Maffei, Fábio; Muniz, Fábio; Freitas-Filho, Ricardo F.; Costa Gonçalves Portelinha, Thiago; Campos, Zilca; A. B. Bassetti, Luís (Ethnobiology and Conservation, 2021)
Crocodilian-human conflicts, caused especially by urban expansion and habitat destruction, have been considered one of the main threats to the conservation of these species worldwide. In Brazil, such conflicts have been documented with crocodilian species all over the country. This study identified 400 conflict events between humans and caimans within Brazilian cities between 2016 and 2021. Caiman latirostris (57.4%) was the most common species found in large urban centers in the Northeastern and Southeastern regions. Most of the encounters (N = 250) were registered in the rainy season and the rescues were mainly carried out by the environmental military police and fire brigades. The management protocols in the presence of crocodilians in urban areas have been outlined, to be carried out by the Municipal Environmental Secretariats to minimize animal stress and the risk of accidents in urban areas. The increasingly common interaction between humans and caimans in urban environments is an important alert to envisage best conducts for the coexistence between humans and crocodilians and shows the need to invest in public policies to mitigate the effects of cities on wildlife.